High‐resolution temporal dynamic transcriptome landscape reveals a GhCAL‐mediated flowering regulatory pathway in cotton (Gossypium hirsutum L.) - Cheng, Shuaishuai (Plant Biotechnol J, 2020)
The transition from vegetative to reproductive growth is very important for early maturity in cotton. However, the genetic control of this highly dynamic and complex developmental process remains unclear. A high‐resolution tissue‐ and stage‐specific transcriptome profile was generated from six developmental stages using 72 samples of two early‐maturing and two late‐maturing cotton varieties. The results of histological analysis of paraffin sections showed that flower bud differentiation occurred at the third true leaf stage (3TLS) in early‐maturing varieties, but at the fifth true leaf stage (5TLS) in late‐maturing varieties. Using pairwise comparison and weighted gene co‐expression network analysis, 5312 differentially expressed genes were obtained, which were divided into 10 gene co‐expression modules. In the MElightcyan module, 46 candidate genes regulating cotton flower bud differentiation were identified and expressed at the flower bud differentiation stage. A novel key regulatory gene related to flower bud differentiation, GhCAL, was identified in the MElightcyan module. Anti‐GhCAL transgenic cotton plants exhibited late flower bud differentiation and flowering time. GhCAL formed heterodimers with GhAP1‐A04/GhAGL6‐D09 and regulated the expression of GhAP1‐A04 and GhAGL6‐D09. GhAP1‐A04‐ and GhAGL6‐D09‐silenced plants also showed significant late flowering. Finally, we propose a new flowering regulatory pathway mediated by GhCAL. This study elucidated the molecular mechanism of cotton flowering regulation and provides good genetic resources for cotton early‐maturing breeding.